Correlation of Microalbuminuria with Estimated GFR (eGFR) by Cockcroft–Gault and MDRD Formula in Type 2 Diabetics and Hypertensives - Saha, T. K. (Indian J Clin Biochem, 2014)
Increase in urine albumin excretion rate (AER) precede a fall in glomerular filtration rate in patients developing diabetic chronic kidney disease (CKD). Our results have shown that 7 (50 %) of diabetic and hypertensive individuals with decreased GFR do not have increased AER. In this cross-sectional study, we measured AER of 75 patients with type 2 diabetes and hypertension by immunoturbidimetric method. We correlated the results with eGFR values obtained by Cockcroft–Gault and MDRD method. The method used was not a compensated method. We measured serum creatinine by modified Jaffe’s kinetic method in autoanalyzer XL-600. Analysis of data showed positive correlation between eGFR and microalbuminuria by both the methods with eGFR <60 mL/min/1.73 m(2). Pearson’s correlation co-efficient (r) was 0.9 (p = 0.0001) by Cockcroft–Gault formula and 0.69 (p = 0.0063) by MDRD formula. Our results concluded that there was positive correlation between AER and eGFR <60 mL/min/1.73 m(2). We have recognized that these two parameters provide a complimentary benefit in management of cases with CKD.